Adaptasi, Inovasi, Dan Pengembangan Kompetensi Sdm Di Era Transformasi Digital - Nurrahma, Dhea Isnaeni; Febrianti, Revana; Devi, Serli Marlita; Alfizi, Alfizi (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The rapid advancement of digital technology has driven a major transformation in human resource (HR) management, requiring organizations to adapt swiftly through innovation and continuous competency development. This study aims to identify and analyze the challenges faced by HR in the digital transformation era, focusing on individual and organizational adaptation, innovation in HR management, and competency enhancement through lifelong learning. The research employs a literature review method with a descriptive qualitative approach, examining relevant scholarly works published within the last decade. The findings reveal that digital transformation requires HR professionals not only to master technical and digital skills but also to possess critical thinking, creativity, collaboration, and adaptability in a dynamic work environment. Innovations through digitalization of HR processes, the use of artificial intelligence (AI) and big data, and the implementation of flexible work systems serve as key strategies to strengthen organizational competitiveness. However, challenges remain, including digital skill gaps, cultural resistance, and the need for transformational leadership. Therefore, competency enhancement through reskilling and upskilling programs, along with fostering a culture of lifelong learning, must be integrated into modern HR policies. This study contributes a comprehensive and integrative conceptual framework on adaptation, innovation, and competency development of human resources in the digital era, which have previously been examined separately in existing literature. Furthermore, it proposes a conceptual model that systematically maps the interrelations among HR challenges, technological adaptation strategies, managerial innovation, and continuous competency enhancement. The study also provides evidence-based policy recommendations that can be implemented by organizations and governments to build an inclusive and sustainable digital human resource ecosystem.